Transnational Europe Promise, Paradox, Limits - DeBardeleben, J.; DeBardeleben, J.; Hurrelmann, A.; Hurrelmann, A. (Palgrave Studies in European Union Politics,, 2011)
Transnational connections are a defining feature of contemporary Europe. They include cross-border economic and cultural exchange, migration, and political activism. This volume probes their political and social significance and makes a case for incorporating transnationalism more systematically into the research agenda of European Studies.